IMPLEMENTASI PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN NOMOR 28 TAHUN 2016 TENTANG SISTEM PENJAMINAN MUTU PENDIDIKAN DASAR DAN MENENGAH DI SMP NEGERI 3 MENGWI - I Rai Wahyudi Putra; Ida Ayu Putu Sri Widnyani (Locus, 2020)
In accordance with the Minister of Education and Culture Regulation No. 28 of 2016, the quality assurance system for primary and secondary education aims to ensure the fulfillment of standards in the education unit systematically, holistically, and sustainably, so that the culture grows in the education unit independently. The problems of this study are: 1. How is the implementation of the Minister of Education and Culture Regulation No. 28 of 2016 concerning the quality assurance system for primary and secondary education in SMP Negeri 3 Mengwi, 2. What factors are hampering the implementation of Minister of Education and Culture Regulation number 28 of 2016 concerning the quality assurance system for primary and secondary education in SMP Negeri 3 Mengwi. This research is a qualitative research. In this study the authors found several research results, namely: 1. At SMP Negeri 3 Mengwi, the education quality mapping process has been carried out, namely by using an internal quality mapping system conducted by the School through the dapodik system, which contains all School data and annually completes the quality mapping questionnaire by utilizing the quality mapping application and the results of the quality mapping process. this is a school having a School quality mapping report card. From the report card, it can be seen how the school quality conditions are in accordance with 8 Education Quality Standards. Every 5 years the quality mapping process is also carried out by the National Accreditation Board of the Provincial Government. 2. The obstacles in implementing Permendikbud No. 28 2016 are the obstacles that occur from environmental conditions both within the School's internal environment and from the School's external environment.